Development of a Hydroxyurea Decision Aid for Parents of Children With Sickle Cell Anemia. Issue 1 (January 2019) - Crosby, Lori E.; Walton, Ashley; Shook, Lisa M.; Ware, Russell E.; Treadwell, Marsha; Saving, Kay L.; Britto, Maria; Peugh, James; McTate, Emily; Oyeku, Suzette; Nwankwo, Cara; Brinkman, William B.
Abstract : National evidence-based guidelines recommend offering hydroxyurea to patients with sickle cell anemia 9 months of age and older using shared decision making, but offer no strategies to aid implementation. We developed a hydroxyurea multicomponent decision aid via a needs assessment, clinic observations, and iterative feedback to address parent decision needs and promote a discussion between clinicians and parents. A total of 75 parents and 28 clinicians participated across all phases. The decision aid was rated as useful. Hydroxyurea knowledge improved and decisional conflict decreased supporting the potential for use to facilitate shared decision making in pediatric sickle cell anemia.